NEW TYPES OF FLAME RETARDANTS BASED ON PHOSPHATE DERIVATIVES (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
One of the main problems of nature conservation and protection of the environ-ment is the reducing of flammability of natural and synthetic materials as well as products based on them. In order to obtain non-combustible materials such as flame retardants, monosodium salt of orthophosphoric acid, urea, thiourea and their mono-methylol derivatives, as well as N-monomethylol acrylamide were used in this work. The reaction for the synthesis of the mentioned compounds was carried out in the presence of a small amount of water. During the reaction between urea and monosodium salt of orthophosphoric acid, ammonia and СО2 were released. In the case of the reaction of thiocarbamide with the monosodium salt of orthophosphoric acid, in addition to ammonia and CO2, hydrogen sulfide is partially released, the formation mechanism of which is presented in the work.
Keywords: flame retardants; urea; thiourea; N-monomethylol acrylamide